STRATEGI PENGEMBANGAN USAHATANI CABAI BESAR (Capsicum annuum var longum) DI DESA LUBUK LEBAN KECAMATAN SOSOH BUAY RAYAP KABUPATEN OGAN KOMERING ULU (JASEP, 2018)
This research is to know Internal factors (strengths and weaknesses) and External factors (opportunities and threats) and development of large chili farming (capsicum annuum) and to analyze the strategy of big chili farming in Lubuk Leban Village Sosoh Buay Termap Sub-district of Ogan Komering Ulu Regency. Data processing is done by using SWOT Analysis to know the internal factors as well as what external factors related to the development of large chili farming and to analyze the strategy of the development of large chili farming. Based on the result of the research, it is known that internal factor of big chilli farming development is with the strength (Has wide area for big chili farming, Availability of big cultivation of cabbage cultivation, knowledge of farmers in large cebe farming to produce big cebe good) and with weakness The lack of technology in the haze or agro- industry sector, the lack of tools of transortation) and the extension factor of the development of large chili farming is by chance (expensive price of chilies, generating hiliration, the application of MEA (ASEAN Economic Community) and with threat (Larger cultivation of large chilli pepper, Extensive cultivation of large pepper cultivation), ST strategy (improving the quality of large chilli, improving the quality of hilirisasi product yield etc.), WO strategy (optimizing partnerships with marketing institutions, the need for government or private tools to generate more hilirations that can be generated by large chili farming), WT strategy (Need for capital assistance from the government related to the cultivation and processing of large chili , Conducting training and counseling related to the processing of large chili plants.